Math, asked by kavya98, 1 year ago

Solve ax+by=c, bx+ay=1+c



Answers

Answered by mysticd
309

Answer:

 x =\frac{ac-b-bc}{a^{2}-b^{2}}

 y = \frac{a+ac-bc}{a^{2}-b^{2}}

Step-by-step explanation:

Given system of equations:

ax+by=c ---(1)

bx+ay=1+c ----(2)

multiply equation (1) by a, and equation (2) by b , we get

x+aby=ac---(3)

x+aby=b+bc---(4)

Subtract (4) from (3) , we get

(-b²)x= ac-b-bc

\implies x =\frac{ac-b-bc}{a^{2}-b^{2}}

Now,

multiply equation (1) by b, and equation (2) by a , we get

abx+y=bc---(5)

abx+y=a+ac---(6)

Subtract (5) from (6), we get

(-b²)y = a+ac-bc

\implies y = \frac{a+ac-bc}{a^{2}-b^{2}}

Therefore,

 x =\frac{ac-b-bc}{a^{2}-b^{2}}

 y = \frac{a+ac-bc}{a^{2}-b^{2}}

•••♪

Similar questions